Multi-Channel Electrolyte Supply for Electrochemical Trepanning of Blisks Using Rotational Feeding Combined with Shift Feeding - Gaopan Lei; Dong Zhu; Mingzhu Ren; Erhao Jiao; Yongquan Xie; Mingfu Li (Chinese Journal of Mechanical Engineering)
Abstract Rotational feeding combined with shift feeding electrochemical trepanning (RF-SF ECTr) is an effective method for machining aeroengine blisks. However, given the variable relative motion of the electrodes and the complex flow channels around the bending and twisting blades, the accessibility and uniformity of the flow field are poor in blisk RF-SF ECTr using the traditional electrolyte supply (TES) mode, resulting in poor machining stability and low machining efficiency. To improve the distribution of the flow field, a new multi-channel electrolyte supply (MCES) mode is proposed for blisk RF-SF ECTr, in which the position and volume of the electrolyte supply are controlled effectively by setting multiple inlet channels in the liquid inlet area. A flow-field simulation comparison between TES and MCES shows that better accessibility and uniformity of the flow-field distribution are achieved under MCES. To clarify further the flow-field distribution characteristics under RF-SF ECTr, a series of flow-field simulations was conducted at different machining depths. Based on the obtained dynamic change law for the flow field, to enhance further its uniformity and accessibility, a global coverage strategy for the electrolyte supply and a flow-field structure optimization method for MCES are proposed, which involve optimizing the number, diameter, and location of the inlet channels. After many simulations, the optimal MCES structure was achieved whereby the electrolyte covers all positions effectively in the processing area. To verify the proposed method as effective and correct, a series of RF-SF ECTr experiments was carried out. Under the optimized MCES mode, the feeding rate was increased from 0.8 mm/min with the TES mode to 2.0 mm/min, and the processing stability and efficiency were improved significantly. The methods presented here offer an effective guide for flow-field optimization when machining other components with complex spatial structures.